2005
DOI: 10.1143/jjap.44.1621
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Poly(vinylalcohol) Nanocomposite Film Devices: Applications for Femtosecond Fiber Laser Mode Lockers and Optical Amplifier Noise Suppressors

Abstract: We fabricated single-wall carbon nanotube (SWNT)/poly(vinylalcohol) (PVA) nanocomposite freestanding films and examined their application in devices in which the saturable absorption of SWNTs at near-infrared optical telecommunication wavelengths can be utilized. In a passively mode-locked fiber laser, we integrated a 30-µm-thick SWNT/PVA film into a fiber connection adaptor with the film sandwiched by a pair of fiber ferrules. A ring fiber laser with a SWNT/PVA saturable absorber was operated very easily in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 27 publications
(47 reference statements)
1
57
0
Order By: Relevance
“…The sprayed solution spread around the target position where we want to deposit CNTs. After the proposal, direct synthesis method (Yamashita et al, 2004) and polymer embedding method (Sakakibara et al, 2005) have been reported. Though embedding CNTs into polymer materials have been already demonstrated (Sakakibara et al, 2003), the report was the first application to the passive mode-locker in the fiber-end-type configuration.…”
Section: Cnt Based Optical Device Structures and Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sprayed solution spread around the target position where we want to deposit CNTs. After the proposal, direct synthesis method (Yamashita et al, 2004) and polymer embedding method (Sakakibara et al, 2005) have been reported. Though embedding CNTs into polymer materials have been already demonstrated (Sakakibara et al, 2003), the report was the first application to the passive mode-locker in the fiber-end-type configuration.…”
Section: Cnt Based Optical Device Structures and Fabrication Methodsmentioning
confidence: 99%
“…Since CNTs are nano-sized material, one of the largest problems to realize CNT-based devices is handling issue. Optical deposition method has an advantage in efficiency over the other handling methods, such as spraying (Set et al, 2004a;Set et al, 2004b), direct synthesis (Yamashita et al, 2004), and polymer embedding methods (Sakakibara et al, 2005). These methods mostly require complicated processes, large-scale setups, and dissipate significant numbers of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the chirality of SWNTs, they can be either metallic or semiconducting, the latter being the desired behavior for nonlinear optical performance. Many optical applications could benefit from using SWNTs as nonlinear materials, such as noise suppression, wavelength conversion, and passive mode-locking [1][2][3]. A challenge when designing SWNT-based devices is incorporating the nanotubes in such a way as to enhance their interaction with light.…”
mentioning
confidence: 99%
“…The Bragg wavelength is directly proportional to the grating period, so great flexibility in setting the wavelength emission of a DFB laser is accomplished when writing Bragg gratings. The most widespread methods to inscribe Bragg gratings in optical fibers are the two-beam interferometric method [44] and the phase mask method [45,46], both based on the irradiation of periodic patterns of UV light upon photosensitive fibers.…”
Section: Distributed Feedback Fiber Lasersmentioning
confidence: 99%
“…CNT-based absorbers can be fabricated to operate both in transmission or reflection, which allows the use of either ring or linear cavity configuration [31]. Integration of nanotubes in optical cavities has been approached with different techniques, such as free-space [31,46], fiber-end [47], waveguide [48], and fiber structures [49][50][51].…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 99%